The Occurrence of Seedlessness in Higher Plants; Insights on Roles and Mechanisms of Parthenocarpy - Picarella, Maurizio E.; Mazzucato, Andrea (Frontiers in Plant Science, 2019)
Parthenocarpy in a broad sense includes those processes that allow the production of seedless fruits. Such fruits are favourable to growers, because they are set independently of successful pollination, and to processors and consumers, because they are easier to deal with and to eat. Seedless fruits however represent a biological paradox because they do not contribute to offspring production. In this work, the occurrence of parthenocarpy in Angiosperms was investigated by conducting a bibliographic survey. We distinguished monospermic (single seeded) from plurispermic (multiseeded) species and wild from cultivated taxa. Out of 96 seedless taxa, 66% belonged to plurispermic species. Of these, cultivated species were represented six times higher than wild species, suggesting a selective pressure for parthenocarpy during domestication and breeding. In monospermic taxa, wild and cultivated species were similarly represented. The occurrence of parthenocarpy in wild species suggests that seedlessness may have an adaptive role. In monospermic species, seedless fruits are proposed to reduce seed predation through deceptive mechanisms. In plurispermic fruit species, parthenocarpy may exert an adaptive advantage under suboptimal pollination regimes, when too few embryos are formed to support fruit growth. In this situation, parthenocarpy offers the opportunity to accomplish the production and dispersal of few seeds, thus representing a selective advantage. Approximately 20 sources of seedlessness have been described in tomato. Excluding the EMS induced mutation parthenocarpic fruit (pat), the parthenocarpic phenotype always emerged in biparental populations derived from wide crosses between cultivated tomato and wild relatives. Following a theory postulated for apomictic species, we argument that wide hybridization could also be the force driving parthenocarpy, following the disruption of synchrony in time and space of reproductive developmental events, from sporogenesis to fruit development. The high occurrence of polyploidy among parthenocarpic species supported this suggestion. Other commonalities between apomixis and parthenocarpy emerged from genetic and molecular studies of the two phenomena. Such insights may improve the understanding of the mechanisms underlying these two reproductive variants of great importance to modern breeding.